Computer simulation of gear cutting and strength analysis with special regard to extremely low teeth numbers - Tesfaye, Tamrat; Gerner, Dieter (Zede Journal of Ethiopian Engineers and Architects, 2023)
The involute gear system is widely used by gear manufacturers for spur and -helical gear in mechanical power transmissions. This is because of its advantages in standardization, machining, high efficiency and adaptability to load and center distance. For mechanical power transmission, involving high speed a maximum, gear ratio in one step and pinions with minimum possible teeth number are recommended Usually, extremely low teeth numbers, particularly for rack and pinion, are not treated in detail in the literature. These are of interest for cases of slow moving machines or manually operated mechanisms where lifetime and uniformity of motion is not crucial, but a bigger gearing ratio of single gear set for achieving cheap and small transmissions is important. For such gears with small number of teeth, modifications of parameters like teeth number, profile co"ection, undercut, head shortening, rack pressure angle and their interactions are investigated An instructive computer-based modeling of involute gear cutting using the gear generation method is given preference over purely theoretical investigations. A number of gear dimensions are taken from the modeled gears and conclusions are drawn from them. Except mentioning some important features, there is no intention to represent in this article the internationally acknowledged involute gear system and its definitions in detail which can be studied separately.